MULTIMEDIA APPLICATION NAME OF ANIMAL IDENTIFICATION OF LEARNING IN ENGLISH USING MICROSOFT VISUAL BASIC VERSION 6.0. - Eko Teguh Wibowo (Jurnal Sistem Informasi, 2007)
Multimedia is a combination of the components of the information in the form of images, text, sound and animation are stored and processed in a computer. An application that contains only one component can still be called multimedia. English is the language of international standards, each person required to be mastered. In addition to supporting business activities, the English language is also frequently used in everyday social intercourse, with control of our English language will feel confident. Introduction of multimedia applications Learning Animal names in English is an application that provides information about the animal names in English. This application also includes sound and animation of each animal are shown. In making this application the author using the programming language Visual Basic 6.0 as well as several design programs, among others SWiSHmax and Photoshop 7.0.